The Important Role of Principal in Academic Supervision to Improve Teacher Competency in Society 5.0 Era - Sukmara, Ganda; Yuliana, Lia; Retnowati, Endah; Jannah, Nita Maghfiratul (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
This research analyzes theories and strategies for increasing teacher competency through academic supervision. This research used a qualitative literature review method. The collected articles were selected using purposive sampling, resulting in 120 relevant books and articles. The document findings were then analyzed and sorted into three main topics: educational supervision, teacher competency, and the era of society 5.0. After grouping the data based on the themes above, 10 articles and books were found on topics related to educational supervision, 10 articles and books on teacher competency, and 5 on the era of society 5.0. The research results show that school (madrasah) principals must have expertise and seriousness in supervising educational institutions, especially academic supervision, which aims to improve teacher competence. Academic supervision involves planning, implementation, and evaluation with the principles of objectivity and continuous improvement. With this research, it is hoped that it can be used as a model for effective academic supervision by school principals and teachers in the information technology era.